El poder de la palabra - Hervé, Francisco, 1971-; Brahm, Sebastián; Leighton, Pablo (Panchito Films, 2009)
Hardy sells trinkets on the buses in Santiago. In 2005, a government project worries him: soon we will be a "world class" country, so we will not be able to continue tolerating his trade. Hardy gathers two thousand colleagues and together they fight not to be marginalized by modernity.--